2023
DOI: 10.3390/diseases11010022
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive Craniectomy in Severe Traumatic Brain Injury: The Intensivist’s Point of View

Abstract: Introduction: Traumatic brain injury (TBI) represents a severe pathology with important social and economic concerns, decompressive craniectomy (DC) represents a life-saving surgical option to treat elevated intracranial hypertension (ICP). The rationale underlying DC is to remove part of the cranial bones and open the dura mater to create space, avoiding secondary parenchymal damage and brain herniations. The scope of this narrative review is to summarize the most relevant literature and to discuss main issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…We observed a temporal association between cerebral autoregulation results and decompressive craniectomy/external ventricular drain placement. At our institution, decompressive craniectomy (primary or secondary) [ 18 ] is typically performed for patients with intracranial hypertension, and external ventricular drains are used for intermittent cerebrospinal fluid drainage (also known as "burping" of cerebrospinal fluid). Kolias et al [ 19 ] demonstrated in a case series that decompressive craniectomy after TBI led to a reduction in ICP and improved CBF.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a temporal association between cerebral autoregulation results and decompressive craniectomy/external ventricular drain placement. At our institution, decompressive craniectomy (primary or secondary) [ 18 ] is typically performed for patients with intracranial hypertension, and external ventricular drains are used for intermittent cerebrospinal fluid drainage (also known as "burping" of cerebrospinal fluid). Kolias et al [ 19 ] demonstrated in a case series that decompressive craniectomy after TBI led to a reduction in ICP and improved CBF.…”
Section: Discussionmentioning
confidence: 99%
“…The rst known written account of this decompressive surgery was provided by Annandale in 1894, but Thomas Kocher rst used it in 1901 to treat RICH. [2,14,16,47] In 1905, Harvey Cushing published a detailed report on subtemporal and suboccipital decompression to relieve RICH in patients with inoperable brain tumors. [20] DC lost popularity during the 1970s due to disappointing results.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Oedema can be vasogenic or cytotoxic, the latter being more frequently associated with TBI. 13 It can lead to increased intracranial pressure and herniation. 14 Herniation is the result of mass effect of either primary lesions (eg subdural haematoma, intracerebral haemorrhage) or secondary ones (eg cerebral oedema) that force the brain to “slide” through anatomical “gateways”.…”
Section: Relevant Sectionsmentioning
confidence: 99%